مشكلة الاندماج الوطني في إفريقيا: دراسة حالة منطقة القرن الإفريقي - دخالة, مسعود; بن عيسى, صفاء (جامعة الوادي.University eloued, 2022)
يتناول هذا المقال أحد أهم المشكلات التي واجهت الدول الأفريقية عموما ودول منطقة القرن الأفريقي على وجه الخصوص ألا هي مشكلة الاندماج الوطني، وبخاصة بعد حصولها على الاستقلال وشروعها في بناء الدول الوطنية الحديثة . فقد قام الاستعمار الاوروبي بتقسيم دول المنطقة ووضع حدود اصطناعية لها دون مراعات مكوناتها الاجتماعية والقبيلية وهذا ما شكل فيما بعد قنابل موقوتة، بحيث انتجت تلك التقسيمات دول مشكلة من اثنيات متنوعة وكل اثنية تحاول السيطرة على السلطة السياسية و الاجتماعية والسياسية والاقتصادية وقبل كل شيء السلطة العسكرية في مقابل الاثنيات الاخرى، وقد نتج عن هذه المشكلات الخطيرة ضعف أداء الدولة الوطنية في المجالات الاقتصادية والاجتماعية و السياسية ، وكذا دخولها في صراعات اثنية داخلية وبينية وهذا ما جعلها تعد نموذجا بارزا للدول الفاشلة في العالم. This article addresses one of the most important problems faced by African States in general and those of the Horn of Africa region in particular, not being the problem of national integration, especially after they have gained independence and begun to build modern national States. European colonialism divided the States of the region and established artificial boundaries without taking into account their social and tribal components. political, social, political, economic and above all military power versus other ethnicities, so that these divisions have produced complex States of diverse ethnicities and all ethnicities that attempt to control political, social, political and economic power, These serious problems have resulted in the weak performance of the national State in the economic, social and political spheres as well as its engagement in internal and inter-ethnic conflicts, which has made it a prominent example of the world's failed States.
Keywords: افريقيا ; القرن الافريقي ; مشكلة الاندماج ال ; طني ; الد ; لة ال ; طنية; Africa " Horn of Africa; integration problem " tonny; Father; ll; Hellenic